Heterogeneous detection of circulating tumor cells in patients with colorectal cancer by immunomagnetic enrichment using different EpCAM-specific antibodies - Antolovič, Dalibor; Galindo Escobedo, Luis Vidal; Carstens, Anina; Rahbari, Nuh Nabi; Büchler, Markus W.; Weitz, Jürgen; Koch, Moritz (BMC biotechnology, 2010)
Circulating tumor cells (CTC) and disseminated tumor cells (DTC) are thought to be responsible for metastasis, so the detection of CTC may serve as individual prognostic factor in patients suffering from colorectal cancer. Therefore, a series of immunomagnetic enrichment methods for CTC have been developed using a variety of monoclonal antibodies against the Epithelial Cell Adhesion Molecule (EpCAM). However, it remains unclear whether all commercially available EpCAM antibodies show the same sensitivity and specificity. Furthermore, it remains unclear which method of sample preparation and cell extraction is most suitable for immunomagnetic enrichment and detection of CTC. In this study, we aimed to investigate whether the detection of CTC by a cytokeratin 20 reverse transcriptase-polymerase chain reaction (CK20 RT-PCR) may be influenced by the use of various Epithelial Cell Adhesion Molecule (EpCAM) antibodies for immunomagnetic isolation of CTC.
Gesehen am 23.11.2022